2005
DOI: 10.1209/epl/i2005-10138-7
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Griffiths effects in metallic systems

Abstract: We show that two apparently contradictory theories on the existence of Griffiths-McCoy singularities in magnetic metallic systems [1,2] are in fact mathematically equivalent. We discuss the generic phase diagram of the problem and show that there is a non-universal crossover temperature range T * < T < ω0 where power law behavior (Griffiths-McCoy behavior) is expect. For T < T * power law behavior ceases to exist due to the destruction of quantum effects generated by the dissipation in the metallic environment… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 17 publications
3
22
0
Order By: Relevance
“…Likewise, as we previously claimed for Fe2+xV1−xAl near the paramagneticferromagnetic QCP at x  0.05 [12,21], the low-temperature enhancement in C/T that we observed at x  −0.05 and the singular temperature dependence, approximated by T −1 , can be reminiscent of a Griffiths-McCoy singularity near the QCP (Fig. 4(a)) [26]. As indicated below, there was an obvious MI transition in the vicinity of x = −0.05 and T < 0.25 K. The exponent(x) obtained from low-temperature specific heat data showed the characteristic features expected for a Griffiths phase [26]; that is,  was approximately 0 at the quantum critical point of xMIT and recovered to that of a Fermi liquid  1, with increasing distance from the QCP (Fig.…”
Section: Specific Heatsupporting
confidence: 88%
See 2 more Smart Citations
“…Likewise, as we previously claimed for Fe2+xV1−xAl near the paramagneticferromagnetic QCP at x  0.05 [12,21], the low-temperature enhancement in C/T that we observed at x  −0.05 and the singular temperature dependence, approximated by T −1 , can be reminiscent of a Griffiths-McCoy singularity near the QCP (Fig. 4(a)) [26]. As indicated below, there was an obvious MI transition in the vicinity of x = −0.05 and T < 0.25 K. The exponent(x) obtained from low-temperature specific heat data showed the characteristic features expected for a Griffiths phase [26]; that is,  was approximately 0 at the quantum critical point of xMIT and recovered to that of a Fermi liquid  1, with increasing distance from the QCP (Fig.…”
Section: Specific Heatsupporting
confidence: 88%
“…These inconsistencies with the J = 3/2 cluster model can be explained reasonably well by the fact that the antisite Fe occupying the V site facilitates the establishment of itinerant (ferromagnetic) features in Fe2+xV1−xAl at x > 0 [12] and the fact that an inhomogeneous state (Griffiths phase) that appears to consist of ferromagnetic and paramagnetic clusters emerges at 0 < x < xc m [21]. In a theoretical study, Neto et al found that a Schottky anomaly in the specific heat, due to a magnetic field, appears close to the QCP for magnetic ordering in magnetic metallic systems [26].…”
Section: Specific Heatmentioning
confidence: 99%
See 1 more Smart Citation
“…5(b)] at a temperature slightly higher than T C . It was theoretically obtained by Neto et al 28 that the low-temperature divergence is strongest at the QCP (λ = 0) and the Fermi liquid characteristics (λ = 1) are established far from the QCP. Although it would be still controversial whether the C/T upturn at the zero field is due to a distribution of magnetic anisotropies in paramagnetic clusters 3 or due to proximity to the ferromagnetic QCP, 26 Actually, at x = 0.05 resistivity, ρ(T ) shows NFL behavior: ρ − ρ 0 = A T n , with n < 2 as shown in Fig.…”
Section: Methodsmentioning
confidence: 95%
“…For Ising symmetry, which is relevant for the heavy-Fermion systems as most of them have sizeable spin anisotropies, the damping causes the rare regions to freeze leading to a smeared transition rather than quantum Griffiths effects [60][61][62]. Later, Castro Neto and Jones refined their theory by including the damping [282,283]. They found that for sufficiently weak damping there will be a crossover temperature T * .…”
Section: Methodsmentioning
confidence: 99%